Analysis of eardrum pathologies using the finite element method - Gentil, Fernanda (2019)
This work investigates the effect of eardrum perforations and myringosclerosis in the mechanical behavior of the tympano-ossicular chain. A 3D model for the tympano-ossicular chain was created and different numerical simulations were made, using the finite element method. For the eardrum perforations, three different calibers of perforated eardrums were simulated. For the micro perforation (0.6 mm of diameter) no differences were observed between the perforated and normal eardrum. For the numerical simulation of the eardrum with the largest perforation caliber, small displacements were obtained in the stapes footplate, when compared with the model representative of normal ossicular-chain, at low frequencies, which is related with major hearing loss in this frequency range. For the numerical simulations of myringosclerosis, the larger differences in the displacement field between the normal and modified model were obtained in the umbo. When observing the results in the stapes footplate, there were no significant differences between the two models, which is in accordance to the clinical data. When simulating an eardrum perforation along with myringosclerosis, there is a decrease in the displacements, both from the umbo and the central part of the stapes footplate, often associated with a pronounced hearing loss. It could be concluded that the reduced displacement of the stapes footplate may be related to a greater hearing loss.